(untitled) (LACCEI, 2024)
The high level of competitiveness seen subjected to modern industry, causes companies to constantly speed up and rethink their operational processes in the company. Within it, one of the largest strategies is the application of continuous improvement, applying very useful tools when diagnosing a process of poor or efficient process. Design a methodology continuous improvement on it. Various tools were used of continuous improvement, based on a situational analysis, based on Therefore, the management proposal considers: the design of a adequate methodology for user service processes likewise, a methodology for continuous improvement of the quality in order to generate a budget for the design of the plan. Of In this way, the research concludes that the management design of the continuous improvement methodology is related to and influences directly on the level of customer satisfaction, because if this is managed efficiently progress is made in the processes, personnel relations and procedures final administrative costs of the institution, all this allows us to the optimization of resources and an improvement in profitability of the company The research article aims generally identify the relationship that exists between the improvement continue with profitability